Biochemical changes in whole blood stored for transfusion at Bungoma County Referral Hospital, Kenya - Phidelis M. Marabi; Stanslaus Musyoki; Angela Amayo (AOSIS, 2020)
Background: During storage, transfusion blood may undergo a series of biochemical changes that could pose risks to patients when used. It is important therefore to monitor biochemical changes that may reduce survival or function of stored blood cells. Objective: This study assessed biochemical changes in whole blood stored for transfusion at Bungoma County Referral Hospital in the western region of Kenya between February 2019 and August 2019. Methods: A prospective study design involving 20 randomly selected donor blood units in citrate phosphate dextrose adenine anticoagulant was employed. Biochemical changes were evaluated for 35 days. Potassium and sodium levels were tested using the HumaLyte Plus5 analyser. Blood pH level was estimated using the Hanna pH meter. Results: At the end of the 35 days of storage under blood bank conditions, the mean potassium level significantly increased from 7.31 mmol/L at baseline to 20.14 mmol/L at week 5 (p 0.0001), and the mean sodium level significantly decreased from 150.72 mmol/L at baseline to 121.56 mmol/L at week 5 (p 0.0001). The pH level decreased insignificantly from 7.48 at baseline to 7.38 at the end of week 1 (p = 0.0757) but decreased significantly to 6.15 at the end of week 5 (p 0.0001). Conclusion: Potassium increased and sodium concentrations decreased significantly from the first week of blood storage. The pH decreased significantly from the second week of storage. Therefore, aged blood should be avoided to circumvent potential adverse outcomes from biochemical changes and stored blood should be tested before use.